Examining fall-related mortality in registries and surveillance systems in sub-Saharan Africa: a systematic review - Renz, Alissa; Mayeden, Samuel; Runge-Ranzinger, Silvia; Louis, Valérie R.; Deckert, Andreas; Dambach, Peter; Winkler, Volker; Horstick, Olaf; Wilson, Michael (Injury prevention, 2025)
Objective Fall-related injuries are a global public health concern, and trauma registries aid in collecting data to develop measures to reduce their burden on individuals and communities. The aim of this review was to provide a comprehensive overview of the reporting of fall-related mortality in trauma registries and surveillance systems in sub-Saharan Africa. - Methods A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We searched eight electronic databases, and studies set in countries of sub-Saharan Africa were included if the reported data originated from a trauma registry or surveillance system and contained a measurement of fall-related mortality. Results were synthesised in a descriptive manner. - Results Of the 3574 records found, we included 21 studies in the analysis. Different definitions were inconsistently used in reporting fall-related mortality: studies reported either a percentage of fall deaths by total falls or of fall deaths by total deaths. Deaths due to falls by total falls ranged from 0.01% to 2.4% in studies with paediatric patient populations, and from 0.03% to 60% among studies not restricted to a specific age group. Reporting on other variables in relation to injury and trauma care was also inconsistent. - Conclusions The findings of this review were heterogeneous, and variables were collected irregularly among trauma registries. This led to a broad range of results and made comparisons and deductions difficult. A more standardised data collection across registries would heighten the intercomparability of results from different studies and, therefore, facilitate usage in data-based efforts for implementing prevention and optimising care.